Finite machines, mental procedures, and modern physics - Lupacchini, Rossella (Acta Biomedica Atenei Parmensis, 2007)
A Turing machine provides a mathematical definition of the natural process of calculating. It rests on trust that a procedure of reason can be reproduced mechanically.Turing’s analysis of the concept of mechanical procedure in terms of a finite machine convinced Gödel of the validity of the Church thesis. And yet, Gödel’s later concern was that, insofar as Turing’s work shows that “mental procedure cannot go beyond mechanical procedures”, it would imply the same kind of limitation on human mind. He therefore deems Turing’s argument to be inconclusive. The question then arises as to which extent a computing machine operating by finite means could provide an adequate model of human intelligence. It is argued that a rigorous answer to this question can be given by developing Turing’s considerations on the nature of mental processes. For Turing such processes are the consequence of physical processes and he seems to be led to the conclusion that quantum mechanics could help to find a more comprehensive explanation of them.